Abnormal Return Differences Before And After Amnesty Tax Policy 2016 - 2017 Period II And III (Event Study at Company divided in LQ45 Index) - Hadi Cahyono; Hafiz fitradiansyah` (LPPM of NAROTAMA UNIVERSITY, 2017)
Purpose : The result of this research are expected to provide information to the investors to face the similar event so that investors can make decisions to taking profit in the future. Design/methodology/approach : The model of this event study research is using 45 issuers of LQ45 indexes member during test period for 10 days before and after the event. The statistic test which used in this research is paired sample-test towards CAAR and counting t-test towards AAR.. Findings The result of CAAR is showed that CAAR abnormal return significantly merely happen in research period III. While, for t-test towards AAR showed that abnormal return happened in period II and III tax amnesty execution Research limitations/implications : The object of this research is company which recorded as a member in LQ45 indexes. Practical implications : The result of CAAR is showed that CAAR abnormal return significantly merely happen in research period III. While, for t-test towards AAR showed that abnormal return happened in period II and III tax amnesty execution, with details in period II abnormal return merely happen in t-1 with negative value and period III abnormal return happen in t-9, t-8, t-4, t-3, t+1 and t+9. Originality/value : expected to provide information to the investors to face the similar event so that investors can make decisions to taking profit in the future